Saīsinājumi Anon., Anonym., Anon. Voc. Liborija Depkina vārdnīcas Lettiʃches Wörterbuch manuskriptā - Vanags, Pēteris (Baltistica, 2004)
THE ABBREVIATIONS Anon., Anon. Voc., Anonym. IN LIBORIUS DEPKIN’S MANUSCRIPT Lettiʃches WörterbuchThe article concerns the abbreviations Anon., Anon. Voc., Anonym. in Liborius Depkin’s (1652–1708) manuscript Lettisches Wörterbuch. A comparison of lexemes described with this abbreviation with other anonymous lexicographic sources of the turn of the 17–18th centuries shows clearly that the material described with Anon., etc. is taken from the quadrilingual dictionary Vocabularium published in 1688 in Riga. The abbreviation Anon. used by Liborius Depkin bears witness to the fact that he did not know in 1704 who was the author of this dictionary, thereby strengthening the view already expressed earlier by Kārlis Draviņš that we can't consider Georg Dressel (1654–1698) as the author of it.
Keywords: latvių kalba; senieji raštai